The Macedonian Question: A Historical Overview - Vasilevska, Ivanka (Iustinianus Primus Law Journal - Law Review, 2019)
In the second half of the XIX century on the Balkan political stage the Macedonian question was separated as a special phase from the great Eastern question. Without the serious support by the Western powers and without Macedonian millet in the borders of the Empire, this question became a real Gordian knot in which, until the present times, will entangle and leave their impact the irredentist aspirations for domination over Macedonia and its population by the Balkan countries – Greece, Bulgaria and Serbia. The consequence of the Balkan wars and the World War I was the territorial dividing of ethnic Macedonia. After the collapse of the Ottoman Empire, the territory of Macedonia was divided among Serbia, Greece and Bulgaria, an act of the Balkan countries which, instead of being sanctioned has received an approval, with the confirmation of their legitimacy made with the treaties introduced by the Versailles world order. Divided with the state borders, after 1919 the Macedonian nation was submitted to a severe economic exploitation, political deprivation, national non-recognition and oppression, with a final goal - to be ethnically liquidated. In essence, the Macedonian question was not recognized as an ethnic problem because the conditions from the past and the powerful propaganda machines of the three neighboring countries - Serbia, Greece and Bulgaria, made the efforts to make the impression before the world public that the Macedonian ethnicity did not exist, while Macedonia was mainly treated as a geographical term, and the ethnic origin of the population on the Macedonian territory was considered exclusively as a “lost herd”, i.e. as a nation which is either Serbian, Greek or Bulgarian. On the account of this situation during the entire period between the wars, the Serbs, Greeks and the Bulgarians were unified around the position through which they denied the existence of the separate Macedonian identity. Serbia named the Macedonians in the Vardar part “South Serbs”, Bulgaria claimed that the Macedonians were nothing else but purely Bulgarian people, and Greece entitled the Macedonians to be “Slavophonic Greeks”, before finally giving them the name “Bulgarians”. The Macedonian question fell under the shadow of the oblivion by the great European powers which were the creators and signers of the aforementioned international treaties. In this condition, the Macedonian question patiently waited for the next chance to be re-actualized, until the ASNOM held on 2nd of August 1944. It was exactly then where the statesmanship vision, which the Macedonian people carried throughout all the changes and destiny’s temptations, got its expressive form with the creation of federal Macedonia within the borders of the AVNOJ Yugoslavia.
Keywords: Macedonian question, Balkans, ASNOM.